Penerapan Model Pembelajaran Inside Outside Circle untuk Meningkatkan Hasil Belajar Sosiologi - Wendelina S. Missa (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The aim of this research is to (1) describe the application of the Inside Outside Circle (IOC) learning model to improve the sociology learning outcomes of class X B students at SMA Muhammadiyah Kupang. (2) Can applying the Inside Outside Circle (IOC) learning model improve sociology learning outcomes? The benefits of this research are theoretical and practical. This research is classroom action research, including implementation planning, evaluation, and reflection. The subjects of this research were 19 students of class X B SMA Muhammadiyah Kupang. This research was carried out in two cycles, each consisting of two meetings. Data collection techniques were carried out by observation and interview tests. Meanwhile, descriptive statistical analysis techniques are analysis techniques analyzed before being in the field, analysis while in the field, and data reduction. The research results show that the application of the inside-outside circle (IOC) learning model can improve sociology learning outcomes. This is seen before the action of student learning outcomes of 34% or the poor category. After taking action in cycle 1, student learning outcomes were 63% or in the Fairly Good category. Meanwhile, in cycle II, student learning outcomes are 95% or in the Very Good category. Thus, it can be concluded that applying the inside-outside circle (IOC) learning model can improve sociology learning outcomes at Muhammadiyah Kupang High School.